Diagnostic accuracy of direct digital radiography and conventional radiography for proximal caries detection in primary teeth: A systematic review - Sivakumar Nuvvula; Jayachandra Reddy Bhumireddy; Rekhalakshmi Kamatham; Sreekanth Kumar Mallineni (Wolters Kluwer Medknow Publications, 2016)
Objective: The present study was conducted to uncover the diagnostic accuracy of digital versus conventional radiographic methods for the detection of proximal caries in primary teeth. Methods: Two researchers independently involved in the search process to explore Medical Subject Heading terms "dental digital radiography," "dental radiography," "bitewing," "dental caries," and "primary teeth" using PubMed, Cochrane Library, Ovid SP, and SIGLE databases. Search was confined to the articles published in English language only, with time period limit January 1996 to April 2014 and a hand search was performed to retrieve additional citations. Explicit inclusion and exclusion criteria were applied to eliminate undesired studies. Critical appraisal of the retrieved articles was done using the quality rating based on Bader and co-workers criteria. Results: A total of 129 articles were retrieved, among which 4 articles were included. All the four studies included were in vitro, of which two studies attained a high-quality score, whereas the other two attained average, and low scores based on Bader et al.'s criteria. Conclusions: A big lacuna exists in the literature, regarding the evaluation of radiographic systems in primary teeth, suggesting an immediate need for well conducted in vivo studies. The quality of available evidence can be regarded as fair but cannot be suggested to set a baseline, indicating a need to perform high-quality studies in a randomized sample to find out the accuracy of digital and conventional radiographs.